Moulding freedom and erecting responsibility: An article on contentious commemorative structures and heritage in a post-apartheid South Africa (Alternate Horizons, 2024)
After thirty years of democracy, how have South African narratives around freedom shaped our civic and cultural responsibilities towards public heritage and cultural structures? The South African government, over the last thirty years, has attempted and at times succeeded in its responsibility to erect and create new heritage structures and cultural institutions that highlight previously ignored histories and collective memory in post-apartheid South Africa. But cases still appear on the news of contentious commemorative structures being vandalised as will be explored in the case of the ‘Rhodes Must Fall’ movement. These cases of vandalism draw attention to questions such as what should be done with commemorative structures that represent the colonial era and lack of socio-economic transformation.And from a museum and heritage practitioner’s perspective, how should the destruction and vandalism of public structures be perceived and managed? It can be debated that destruction and vandalism form part of heritage structures' natural life in the public domain and add to their changing symbolism. This article argues that, in the end, only the public can decide which parts of their heritage will be represented and displayed in the public domain. That narratives regarding freedom have been shaped so that South Africans now have the ‘freedom’ to remove contentious and unconstitutional cultural structures. But simultaneously, South Africans and heritage practitioners have the constitutional responsibility to preserve heritage, promote dialogue, and prevent indiscriminate and unnecessary destruction. Therefore, responsible freedom in a democratic South Africa should shape collaboration and dialogue with communities and legislative bodies to avoid irresponsible and unnecessary damage to heritage where possible.